2021
DOI: 10.1186/s12871-021-01525-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravenous lidocaine for dose reduction of propofol in paediatric colonoscopy patients: a randomised placebo-controlled study

Abstract: Background Propofol, a widely used sedative in endoscopic procedures, sometimes causes cardiopulmonary complications. Intravenous lidocaine can diminish visceral pain and decrease the dose of propofol. The purpose of this study was to assess the efficacy and safety of intravenous lidocaine in reducing propofol dosage during paediatric colonoscopy. Methods Forty children who underwent colonoscopy were divided into two groups. Lidocaine hydrochloride… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…The propofol requirement and recovery time were significantly lower in the intervention group than in the control group. There was no significant difference between the 2 groups regarding complications such as hypotension, bradycardia, and hypoxia ( 29 ). Conflicting results of these studies and our study can be attributed to intraoperative lidocaine infusion in these studies, different anesthesia methods, and the younger age of our participants.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The propofol requirement and recovery time were significantly lower in the intervention group than in the control group. There was no significant difference between the 2 groups regarding complications such as hypotension, bradycardia, and hypoxia ( 29 ). Conflicting results of these studies and our study can be attributed to intraoperative lidocaine infusion in these studies, different anesthesia methods, and the younger age of our participants.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have indicated favorable effects with fewer adverse effects in favor of combination therapy for sedation during pediatric endoscopy. Ketamine is often used for sedation during this procedure ( 27 ), and IV lidocaine is still being studied as an adjuvant anesthetic for sedation and analgesia ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Badania wykazały znaczną redukcję tego powikłania, kiedy indukcja znieczulenia poprzedzona była podawaniem dożylnej lidokainy [42,43]. Wykazano również możliwość redukcji dawek propofolu podczas wykonywania zabiegów endoskopowych [44,45].…”
Section: Lidokaina W Indukcji Znieczulenia Za Pomocą Propofoluunclassified
“…In terms of awakening time, only the subgroup<18 years benefited from adding lidocaine, while the other two subgroups showed a non-significant difference between propofol/lidocaine and propofol/placebo groups. 1 2 3 4 5 6 7 8…”
mentioning
confidence: 99%